Impact Consumer Knowledge of Purchase Intensity on Consumer Confidence Mediator in Tandasalib.com Company - Arbiansyah, T.P.T; Wibawa, A.B (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
During COVID-19 pandemic, many companies transformed on digital platforms, due to urgent needs, changes consumption patterns with applications digital have grown new companies digital marketing, ease to use and changing patterns of public consumption and needs, tandasalib.com organizations, previously conducting face-direct Christian religious broadcasting, now developing digital service, i.e: accommodate mental health, spirituality, and so on making social media platforms as a forum religious broadcasting, the purpose of this study is determine impact consumer knowledge on purchase intensity with mediators consumer confidence, the research sample used respondents joined Instagram tandasalib.com, and bought service product, the samples is calculated sample size calculator total 250 respondents, accidental sampling, and analysis techniques using structural equation models (SEM) , impact of direct and indirect purchasing intensity. The results of this study no impact consumer knowledge on purchase intensity mediated consumer confidence, afterward no direct and indirect effect consumer knowledge on purchase intensity, and significant direct effect consumer confidence on purchase intensity, concluded at this study consumer knowledge about services they purchase should be tandasalib.com, explaining company's vision, to foster confidence, if consumer confidence has been formed that is offered and beneficial for themselves, they will purchase service product again and a complaint service is responded to well and findout solution problem, then it has impact consumer knowledge on purchase intensity.